Queen Card Learning Strategy in Increasing Student Activeness in Jurisprudence Subjects at MA Tarbiyatut Tholabah Kranji Paciran Lamongan - Alanshari, M Zainuddin; Aristinah, Dewi (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
This research is entitled Queen Card Learning Strategy in Increasing Student Activeness in Fiqh Subjects at MA Tarbiyatut Tholabah Kranji Paciran Lamongan. Queen Card is a learning strategy using cards that have different functions on each side. This strategy is a development of the Jigsaw strategy, only this strategy uses cards as a medium for group formation. The aim of this research is to find out how the Queen Card strategy is used in fiqh subjects at MA Tabiyatut Tholabah Kranji Paciran Lamongan and to find out how active students are in using the Queen Card strategy in fiqh subjects at MA Tarbiyatut Tholabah Kranji Paciran Lamongan. The type of research used is descriptive qualitative, research location at MA Tarbiyatut Tholabah Kranji Paciran Lamongan. The data collection techniques used were observation, interviews and documentation. Meanwhile, data analysis techniques are carried out by means of data reduction, data presentation, and drawing conclusions. Data sources in this research include the principal of MA Tarbiyatut Tholabah, fiqh subject teachers and students. The results of this research, the first to implement the Queen Card strategy, are that students can be more active, interact well, and develop thinking and speaking skills. Second, the Queen Card strategy succeeded in increasing student activity, building good interactions between group friends and between students and teachers, and had a positive impact on increasing students' final grades